ATR4S: toolkit with state-of-the-art automatic terms recognition methods in Scala. - Astrakhantsev, Nikita (Language Resources & Evaluation, 2018)
Automatically recognized terminology is widely used for various domain-specific texts processing tasks, such as machine translation, information retrieval or ontology construction. However, there is still no agreement on which methods are best suited for particular settings and, moreover, there is no reliable comparison of already developed methods. We believe that one of the main reasons is the lack of state-of-the-art method implementations, which are usually non-trivial to recreate—mostly, in terms of software engineering efforts. In order to address these issues, we present ATR4S, an open-source software written in Scala that comprises 13 state-of-the-art methods for automatic terminology recognition (ATR) and implements the whole pipeline from text document preprocessing, to term candidates collection, term candidate scoring, and finally, term candidate ranking. It is highly scalable, modular and configurable tool with support of automatic caching. We also compare 13 state-of-the-art methods on 7 open datasets by average precision and processing time. Experimental comparison reveals that no single method demonstrates best average precision for all datasets and that other available tools for ATR do not contain the best methods.